Children's reading comprehension and assessment - Paris, Scott G., 1946-; Stahl, Steven A. (Center for Improvement of Early Reading Achievement (Series), 2005)
Originating in a CIERA conference at Michigan University, this book examines how readers understand text and how comprehension is assessed. It provides contexts for the study of reading comprehension, examines how vocabulary, motivation, and expertise influence comprehension, and analyses the developmental course and correlates of comprehension.